Philosophical Values in Thornton Wilder’s Our Town - Yuhendra Yuhendra (LINGUA LITERA : journal of english linguistics and literature, 2015)
As one of human’s expressions, literature is used to reflect lives, human behavior and effects of their actions. The objective of this paper is to explore and revealssocial values in one of influential literary works, a play Our Town by Thornton Niven Wilder. The drama was appraised by critics for the messages it has abouthuman life and the playwright was awarded Pulitzer Award in 1938. This drama is claimed as drama which is rich of philosophy about life. This bibliographicalresearch uses descriptive method with qualitative data taken from the script of the drama. It applies philosophical approach to see the values of life reflected in the drama to human. From moral point of view, Our Town has strong messages that people need to learn to appreciate lives and others. The messages are not only meant for the past – when the play was written - but also for the present situation and even future.